Bio-weapons and Bio-terrorism Attacks on Commercial Shipping in Nigeria: The Potential Trojan Horse of the 21st Century - Abdulrazaq O. Abdulkadir (Journal of International Studies, 2016)
Biological attacks by terrorists may seem more like a plot element in an action film than a realistic threat. The possibility of biological weapons attack could be very remote. Scholars are divergent in their opinions on the plausibility of a biological attack. The U.S. Office of the Director of National Intelligence and the National Intelligence Council stated in 2008 that bio-terrorism is a more likely threat than nuclear terrorism. Researches have revealed that of all weapons of mass destruction, biological weapons constitute the greatest worry. The most likely target for bio-terrorism is a major city or other densely crowded areas, such as transportation hubs like sea ports. This paper probes into Nigerian legislations especially the Nigerian Port Authority Act, the NIMASA Act, the Terrorism Act and the NAFDAC Act regarding biological weapons and bio-terrorism in maritime commerce parlance. It is observed in this paper that all these Acts lack preventive mechanisms in the case of the emergence of the scourge. It is argued that Nigeria is vulnerable to bio-terrorism owing to a dearth of detective measure in the boarder ports. The paper concludes that there is an urgent need to revamp the legal framework to tame the threat of bio-terrorism.